Thermal history analysis of granitic rocks in an arc-trench system based on apatite fission-track thermochronology: A case study of the Northeast Japan Arc - Shoma Fukuda; Shigeru Sueoka; Noriko Hasebe; Akihiro Tamura; Shoji Arai; Takahiro Tagami (Journal of Asian Earth Sciences: X, 2019)
We applied apatite fission-track (AFT) thermochronometry to the Cretaceous-Paleogene granitic rocks across the southern part of the Northeast (NE) Japan Arc in order to elucidate the denudation history. As the results, AFT ages were estimated at 79.5–66.0 Ma on the fore-arc side, 29.8–5.5 Ma in the Ou Backbone range (OBR) and 19.1–4.6 Ma on the back-arc side. Thermal inverse modeling with HeFTy offered high-resolution thermal histories, which were converted into denudation rates under the assumption of appropriate geothermal gradients. On the fore-arc side, stable and slow denudation setting (denudation rates < 0.05 mm/yr) was deduced through the Paleogene. On the contrary, in the OBR and on back-arc side, rapid denudation rates from 1 to a few mm/yr were estimated at some localities reflecting the uplift event after 3–2 Ma. Besides, the uplifting style of OBR was constrained from the thermochronometric data; the doming uplift is more plausible than the tilted pop-up style, which was previously suggested based on geological observations. The Iide and Asahi mountains on the back-arc side probably have started to uplift at 3–1 Ma, coeval with the uplift of the OBR. This observation disagrees with the previous tectonic models in which the deformation on the back-arc side initiated at 5–3.5 Ma, prior to the deformation in the OBR. This disagreement possibly suggests a heterogenous tectonic history on the back-arc side. Keywords: Low-temperature thermochronology, Arc-trench system, Apatite fission-track thermochronometry, Northeast Japan Arc, Thermal inverse modeling